Al-Qaeda's female jihadists : the Islamist ideological view - Tuty Raihanah Mostarom (2009)
Unlike their male counterparts, the status of women in radical Islamist ideology is not conducive for participation in the global jihad. Yet there has been a sharp increase in the number of female suicide bombers linked to Al Qaeda. How can this be explained?